SYSTEM OF INTERNAL CONTROL OF REVENUE CYCLE (Study Case At CV. Sinar Terang Distributor) - Denock Kiki Restu Firnanda; Syae fullah (Jurnal Ilmiah Mahasiswa FEB, 2012)
Study was conducted on CV. Sinar Terang Distributor, namely intermediary trading company or sole agent, whereby traders who buy or acquire product first-hand merchandise or supplier directly. CV. Sinar Terang Distributor locations in the city Probolinggo Brantas No. 234. This study aims to identify and analyze the system of internal control over revenue cycle at CV. Sinar Terang Distributor and to know the constraints faced by companies that have been previously applied. This study method is a qualitative descriptive study, the research issue related to the characteristics of the background and the current state of the subject under study, as well as interaction with the environment without involving the calculation of numbers. Based on the results of the study can be said that the implementation of the internal control system of the company’s revenue cycle is very weak. This can be seen from the analysis methods use the framework for internal control structure of The Committee of Sponsoring Organization (COSO), include the analysis environmental control, risk assessment analysis, analysis of control activities, information and communication analysis and monitoring analysis. However, the application of the internal control system over revenue cycle is not immune from the constraints faced by companies such as number of employees, organizational structure, ways of documenting and recording, the availability of space in the wharehouse, which is still minimal equipment and competences of the employees.Key words : Single agent, System of Internal Control, Revenue Cycle, contrainst, qualitative description, framework for internal control structure of The Committee of Sponsoring Organization (COSO).